Mobility enhancement of a high electron mobility transistor by external strain - Omambac, Karim M.
The effect of external strain in the carrier mobility of High Electron Mobility Transistor is investigated. The layer is grown by Molecular Beam Epitaxy at elevated temperatures. High resolution x-ray diffraction of the grown layer revealed that the indium diffused into the Gallium Arsenide substrate. Hall measurements at 10K showed that there is an increase in the mobility of approximately 25 percent. When samples are thinned down to 300um, the mobility at 10K dropped from 45338 cm2/Vs to 33556 cm2/Vs. Reflectivity measurements at 10K of the As-grown layer revealed the splitting of the Heavy hole-Light hole band, indicating that the layer is strained. The separation is about 2.6meV at 10K and broadening of the PL peak in the 1.516ev is observed. The thinned down layer, on the other hand have a lower Heavy Hole-Light Hole band separation indicating that there is less strain. The increase in mobility was attributed to change in the effective mass of the electron in the conduction band when the Heavy Hole-Light Hole is separated.